Working Period As A Moderating Variable Of Work Family Conflict, Work Stress, And Turnover Intention On Counterproductive Work Behavior - Dewi Puspa Amalia; Muhammad Zakiy (Perisai : Islamic Banking and Finance Journal, 2021)
Counterproductive work behavior has caused a lot of harm to the organization and employees, both directly and indirectly. This research aims to determine the effect of work-family conflict, work stress and turnover intention on counterproductive work behavior with tenure as a moderator variable. This research using a purposive sampling technique and took 100 employees of BCA Syariah Bank by distributing questionnaires. The data obtained were analyzed using SmartPLS 3.3. The results of this research are work family conflict, and work stress has a positive effect on counterproductive work behavior, while turnover intention has a negative effect on counterproductive work behavior. The employees who want to resign will maintain their attitude by acting permanently or more productively than usual. The excuse is that employees avoid the penalties and keeps a good track record. In addition, tenure moderates the effect of work-family conflict on counterproductive work behavior.